Out of Order: To Debbie and Dave, Chris and Bill, MJ and John - Katherine Bright (University of Calgary, 2016)
In this paper, a professor and a group of doctoral students reflect on the video Out of Order: Dealing with the Death of a Child, treating the video as research on the topic of grief. The video was shown to the group and then all individuals offered pieces of interpretive writing to represent their understanding of what the â€œparticipantsâ€ in the video were helping us understand about the topic.